Engineering the Winter Soldier: A study of an advanced bionic arm - Keogh, Colin (Superhero Science and Technology, 2022)
The Winter Solider, better known as James Buchanan “Bucky” Barnes, possesses a highly advanced prosthetic arm that provides enhanced levels of strength, endurance, and toughness to the biologically enhanced solider. This paper covers some of the engineering aspects behind his advanced prosthetic. First, the origin of the Winter Solider is discussed with a review of the abilities of his prosthetic arm. These abilities are used to assess the essential characteristics of the arm. An assessment of the anatomical damage suffered by Barnes is presented with this dictating the functionality needed for his prosthetic arm. Some basic assumptions are then made to estimate the material composition of his arm, and thus help identify the real materials that could be used to actually make his arm. This analysis process indicates that early versions of the arm were most likely made from a ferroalloy with a depleted uranium/titanium alloy and tungsten carbides being highly suitable. This is followed by an engineering assessment that breaks down the core aspects of the arm (mechanical structure, actuators, sensors, a power source, and a control system) with discussion on past, present, and future engineering solutions of these core aspects.